THE CONVERSATIONAL IMPLICATURE IN MALAYSIAN TELEVISION SERIES ‘UPIN AND IPIN’ EPISODE 5 - Rizky Yolanda (UIN Sumatera Utara, 2019)
Upin and Ipin is a Malaysian television series of animated short produced by Les’ Copaque Production Sdn. Bhd, which features the life and advantures of the eponymous twin brothers in a fictional Malaysian kampong. This paper is a pragmatics study that aims an investigating conversational implicature in Malaysian television series ‘Upin and Ipin’, mainly used H.P Grice’s theory of conversational implicature. The episodes 5 has chosen as the sample in this study. The writer has found that the implicature occured for 66 times of 113 utterances. This study used qualitative method as the methodology. Based on the Grice’s theory of conversational implicature, implicatures arise from interaction of the following three factors (1) The proposition actually expressed in the utterance, (2) Possibly certain features of the context, and (3) The assumption that the speaker is obeying the rules of conversation to the best of their ability. This study conclude that various types of implicatures were used in Malaysian television series ‘Upin and Ipin’ episode 5.